An Investigation Into Voice Onset And Coda Pronounced By The Second Year Students Of English Major At The University Of Danang, University Of Foreign Languages - Lương Văn Long (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study investigates the pronunciation errors in terms of voice onset and coda (VOT) in English experienced by the second year major students of English at The University of Danang, University of Foreign Language Studies. More specifically, the study attempts to identify the problems encountered by the students when they perform English consonants concerning the initial and final sounds and consonant clusters as well as their modification in the aspects of connected speech. The researcher’s desire is also to make the problem come to light with its causes and suggest some teaching activities to help students improve their performance of the English consonants in terms of VOT. The data were mainly collected from the questionnaires and the diagnostic test in the light of a qualitative and quantitative research using predictive contrastive analysis. Thanks to the generated hypotheses, the study kept a straight line to go deeply into the problem. The study finds that most students of the second year students of